Analysis of the Physical Behavior of the Periodic Mixed-Convection Flow around a Nonconducting Horizontal Circular Cylinder Embedded in a Porous Medium - Muhammad Ashraf; Zia Ullah; Saqib Zia; Sayer O. Alharbi; Dumitru Baleanu; Ilyas Khan (Journal of Mathematics)
An oscillatory mixed-convection fluid flow mechanism across a nonconducting horizontal circular cylinder embedded in a porous medium has been computed. For this purpose, a model in the form of partial differential equations is formulated, and then, the governing equations of the dimensionless model are transformed into the primitive form for integration by using primitive variable formulation. The impact of emerging parameters such as porous medium parameter Ω, Richardson number λ, magnetic force parameter ξ, and Prandtl number Pr on skin friction, heat transfer, and current density is interpreted graphically. It is demonstrated that accurate numerical results can be obtained by the present method by treating nonoscillating and oscillating parts of coupled partial differential equations simultaneously. In this study, it is well established that the transient convective heat transfer, skin friction, and current density depend on amplitude and phase angle. One of the objects of the present study is to predict the mechanism of heat and fluid flow around different angles of a nonconducting horizontal circular cylinder embedded in a porous medium.